2017
DOI: 10.1002/bmc.3997
|View full text |Cite
|
Sign up to set email alerts
|

A comparative pharmacokinetic study of three flavonoids and three anthraquinones in normal and gastrointestinal motility disorders rat plasma after the oral administration of Wei‐Chang‐Shu tablet using high‐performance liquid chromatography–tandem mass spectrometry

Abstract: A simple, fast and reliable high-performance liquid chromatography-tandem mass spectrometry method was developed and validated for the simultaneous quantification and pharmacokinetic study of three flavonoids (liquiritigenin, isoliquiritigenin and formononetin) and three anthraquinones (emodin, rhein and aloe-emodin), which are the bioactive ingredients of Wei-Chang-Shu tablet found in rat plasma. After extraction by liquid-liquid extraction with ethyl acetate, chromatographic separation was achieved on an Agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Emodin has liver protective properties ( 19 ), anti-inflammatory ( 20 , 21 ), and anti-viral effects ( 22 ). It is also associated with immune regulation ( 23 ), promotion of gastrointestinal motility ( 24 ), as well as antioxidant properties ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emodin has liver protective properties ( 19 ), anti-inflammatory ( 20 , 21 ), and anti-viral effects ( 22 ). It is also associated with immune regulation ( 23 ), promotion of gastrointestinal motility ( 24 ), as well as antioxidant properties ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…This research revealed that the plasma contents of 12 prototypical components and one metabolite in the plasma of HQJZ were decreased under the disease condition, while the retention time of flavonoids and flavonoid glycosides became longer in vivo . The pharmacokinetic comparison of three flavonoids (liquiritigenin, isoquiritigenin and formononetin) in WeiChangShu Tablets in normal and gastrointestinal peristaltic rats was consistent with our results, where the AUC (0– t ) , AUC (0–∞) and C max decreased and the T 1/2 increased significantly (Ren et al, 2017). Fang et al found that the AUC (0– t ) and C max decreased and the T 1/2 and MRT (0– t ) increased significantly by comparing the pharmacokinetic parameters of puerarin in healthy and functional dyspepsia patients (Qin et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Traditional Chinese medicine holds the characteristics of being multicomponent and multitarget, and so a PK study of single components cannot reflect its integrity. Wang Guangji et al proposed the T A B L E 1 Comparison of pharmacokinetic parameters of Huangqi Jianzhong Tang (HQJZ) in control and model rats testinal peristaltic rats was consistent with our results, where the AUC (0-t) , AUC (0-∞) and C max decreased and the T 1/2 increased significantly (Ren et al, 2017). Fang et al found that the AUC (0-t) and C max decreased and the T 1/2 and MRT (0-t) increased significantly by comparing the pharmacokinetic parameters of puerarin in healthy and functional dyspepsia patients (Qin et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…The pathogenic factors of gastrointestinal motility disorder are complex. At present, there is no objective criterion for gastrointestinal motility disorder model, but atropine and L-arginine are commonly selected drugs for this model (Ren et al, 2017; Wang et al, 2018). The results of gastric emptying and intestinal propulsion also indicate that L-arginine had inhibited gastric emptying and intestinal propulsion, which indicated that the model of gastrointestinal motility disorder was successful.…”
Section: Resultsmentioning
confidence: 99%